Membangun Keunggulan Kompetitif melalui Platform E-Commerce: Studi Kasus Tokopedia - Sulistyawati, Upik Sri; Munawir (Jurnal Manajemen dan Teknologi, 2024)
This research aims to reveal in depth the key strategies that have enabled Tokopedia, one of the leading companies in the e-commerce industry in Indonesia, to not only build, but also maintain its competitive advantage. Through a comprehensive case study approach, we analyzed various factors that played a role in Tokopedia's success, including product and service innovation, development of a strong ecosystem, and superior customer service. Data for this research was collected through a series of methods, including in-depth interviews with various stakeholders at Tokopedia, careful analysis of financial reports and company publications, as well as an in-depth review of literature related to the e-commerce industry and business strategy. This approach allows us to comprehensively summarize the various factors that play a role in building a strong foundation for Tokopedia's competitive advantage. The results of this research provide invaluable insights for managers and business practitioners in the e-commerce industry, as well as strategic decision makers at various organizational levels. By understanding the key factors that have led to Tokopedia's success, stakeholders can formulate more effective strategies to develop their own competitive advantage in an increasingly fierce and rapidly changing market. Our in-depth analysis reveals that Tokopedia's success is not solely based on a single factor, but is the result of a combination of interrelated and mutually supporting strategies. Apart from product and service innovation which is the company's main focus, developing an inclusive ecosystem is also the key to success.